Effect of the rearing system on the establishment of different functional groups of microorganism in the rumen of kid goats - Paez Lama, Sebastián Antonio (2015)
This study was aimed to determine the effect of the rearing system on the establishment and development of different functional groups of microorganisms in the rumen of kid goats. Fifty kids were fed on goat milk until weaning at 45 (TR, traditional rearing system, n = 25) and 30 days of age (alternative rearing system, AR, n = 25). In addition, only AR group was offered with rumen starter from birth. Both groups consumed alfalfa hay and ground corn between 30 and 90 days of age. Five kids from each group were slaughtered at 21, 30, 45, 70 and 90 days old. It was determined the total number of protozoa, anaerobic, amylolytic and cellulolytic bacteria present in the rumen. Kids of AR were lighter in weight than TR kids between 42 and 56 days old. In both rearing systems, anaerobic and amylolytic bacteria were found at 21 days of age, while cellulolytic and protozoa were not found until 45 days of age. Kids of AR had higher quantities of anaerobic and amylolytic bacteria until 30 and 45 days of age, respectively. These results demonstrate the rearing system does not affect the sequence and time in which the functional groups of microorganisms are established in the rumen. However, the alternative rearing system with early intake of solid food allowed the establishment of greater amount of bacteria and protozoa. Nevertheless, the effect of weaning on growth rate was more marked in kids from alternative rearing system, despite its greater microbiological rumen development.